PRODUCT DEVELOPMENT STRATEGY OF TERASI KAK DAH IN GAMPONG SIMPANG LHEE, KECAMATAN LANGSA BARAT KOTA LANGSA - Salsabila; Adhiana; Wahyu Isnanda Nasution (Jurnal Mahasiswa Agribisnis, 2026)
Terasi Kak Dah in Gampong Simpang Lhee, Langsa City, is a home industry that has been operating since 1998. Despite its longevity, the business still faces several challenges in developing its products, such as limited capital, lack of packaging innovation, and suboptimal promotion. This study aims to analyze suitable product development strategies for Terasi Udang Rebon Kak Dah. The method used is a qualitative approach with SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, with data obtained through observation and interviews using questionnaires.The results indicate that the most relevant strategy is the SO (Strengths-Opportunities) strategy, namely by utilizing strengths such as unique taste, affordable prices, and raw material partnerships to seize opportunities like increased market demand and the development of digital promotion media.One recommended development strategy is product diversification into more practical forms, such as roasted terasi, terasi powder, and various other forms in order to reach a wider and more sustainable consumer base.